KONSTRUKSI MAKNA PENGGUNAAN SMARTPHONE ANDROID SEBAGAI MEDIA KOMUNIKASI DIKALANGAN MAHASISWA ILMU KOMUNIKASI UNIVERSITAS RIAU - Laila Yunita; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The development of communication technology has brought many changes, one which is a mobile phone with the label smart phone (smartphone). Android is one of the types of smartphones are widely used by people at this time Android has many advantages that make many people are interested in using it, one of which is among the students. The use of Android as a communication media among students bring a variety of meanings related to the use of Android itself by them. This study aims to determine the motive, knowledge and understanding of Android applications and communications experience Android users among students of the University of Riau communication.This research method is using a qualitative research method with phenomenological approach. Informants in this study were 10 students of Communication Studies, University of Riau who use Android smartphone selected using purposive technique. Data was collected through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation and conclusion and verification.These results indicate that the motive of communication science students use the Android smartphone as a media communication because they consist of motifs (Because motive) the sense of dissatisfaction, the influence of friends, the look and features of interest, and also because of the need, while the motive for (in order to motives) that facilitate communication, facilitate communication and for existence itself. Knowledge and understanding of Android apps for students of Communication consists of Android as a communication media, Android as media information, and Android as a media presentation of self. Communication experience of communication science students for using Android smartphone consists of exciting experiences (positive experience) and an unpleasant experience (experience negate). An interesting experience for students of science communication using Android are, getting a lot of new friends, to be reunited with old friends as well as the experience of communicating that seemed real. While not a pleasant experience for students of science communication using the Android, Android battery run out quickly, which isnot a good communication network, communication is often misdirected, scams online shop and difficulty in arranging Android device.Keywords: Android, Construction Meaning, Phenomenology.